Pulse type classification by varying contact pressure. - Young-Zoon Yoon (IEEE Engineering in medicine and biology magazine)
The pulse has long been used as a fundamental tool for diagnosis in traditional Chinese medicine. It is generally classified dichotomously as fast or slow, tense or tender, floating or sinking, large or small, empty or full, etc., with each term reflecting a personal constituent or condition of the body. Diagnosis by traditional pulse analysis requires long experience and a high level of skill, and interpretation is subjective, depending on the practitioner. Thus, it would be of great significance to develop a quantitative and systematic measurement scheme to establish an objective diagnostic system for classifying the pulse, which could be used in the practice of traditional Chinese medicine. Here, the authors propose a new quantification scheme of specific pulse characteristics. These characteristics are determined using the pressure-adjusting pulse detector the authors previously developed. This device regulates contact pressure of a sensor (transducer) on the skin over a pulse point by varying the number of weights applied. The weights, 20 g copper disks, 0.5 sq cm, are increased incrementally. The pulse amplitude (as a voltage) is measured by the pressure sensor incorporated into the device. Thus, there is a variable steady-state pressure applied to the pulse point by a sensor, which results in a pulse signal with maximum amplitude dependent on the applied pressure. Advantages of a quantified measurement scheme include a scientific and statistical analysis of pulse data, a more accurate and precise observation of the pulse, and construction of a biophysical model by equations developed from the data. The authors confined their scope here to the introduction of the new quantification method, which they hope to apply for diagnostic purposes in the near future